Atypical femoral fracture in the setting of alendronate treatment for osteoporosis: a case report and literature review - Eric D. Van Baarsel; Vandan Patel; Yazeed Kesbeh; Huthayfa Kahf; Nicholas Alonzo (Greater Baltimore Medical Center, 2019)
Osteoporosis leads to reduced bone mass and disrupted bone architecture. Bisphosphonates are used to treat osteoporosis by inhibiting bone resorption. Chronic bisphosphonate use has been associated with adverse effects including atypical femoral fractures (AFF). We report the case of a 63-year-old woman with a history of osteoporosis treated with alendronate, who presented with bilateral hip and groin pain. Radiography detected a chronic-appearing callus in the left hip concerning for a chronic stress fracture versus malignancy. Initial imaging could not rule out malignancy, prompting positron emission tomography (PET) and bone biopsy. PET scan was negative for malignancy and biopsy found changes consistent with chronic bisphosphonate use. This prompted prophylactic intramedullary nailing of the femur. This case highlights the importance of considering AFF in patients with a history of hip pain in the setting of chronic BPs use and reviews criteria within the literature to manage patients with AFFs.